The mediating effect of good governance on the relationship between e-government and public trust in Lebanon - Alaaraj, Hassan Kamel (2015)
The main objective of this research is to study the mediating effect of good governance on the relationship between e-government and public trust in Lebanon. As an effective tool for economic reform, there is a need to adopt e-government practices to enhance the public trust towards the government. Based on extensive literature review and conceptual background including the theories of institutional-based trust and the diffusion of innovation, the theoretical research framework was developed. Primary data was collected using survey involving 400 Lebanese employees in Beirut. The data have been analyzed using Structural Equation Modeling (SEM). The research findings revealed that eight hypotheses were accepted while five hypothesis were rejected indicating that e-government practices including e-services have a significant and positive effect on both good governance and public trust in Lebanon. However, e-administration has a positive effect on good governance but not on public trust. E-procurement has insignificant effect on both good governance and public trust. Good governance has a positive and significant effect on public trust, but it has no mediating effect on the relationship between e-government including e-administration and public trust. The findings also show that good governance mediates the effect of both e-service and e-procurement on public trust. This research contributes practically by offering practitioners and policy makers in governments the guidelines on how they can empower and build citizens‟ trust by providing efficient, transparent and accountable government services. Future studies are suggested to extend the research empirically in terms of respondents, geographical location and methodology of analysis